Isolation of Pasteurella multocida from chickens, preparation of formalin killed fowl cholera vaccine, and determination of efficacy in experimental chickens (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives:  The  objectives  of  this  study  were  to  isolate  and  identify  Pasteurella multocida  from  fowl  cholera  (FC)  suspected  chicken,  and  to  prepare  and  efficacy determination of formalin killed fowl cholera vaccine using the isolated  P. multocida strain.  Materials and methods: A total of five suspected dead chickens were collected from Brothers  Poultry  Farm  located  at  Gazipur  district,  Bangladesh.  The  samples  were processed  and  the  P.  multocida  was  isolated  through  conventional  bacteriological techniques,  were  finally  confirmed  by  polymerase  chain  reaction  using  P.  multocida specific  primers  targeting  cap  gene.  The  P.  multocida  isolate  was  used  to  develop  a formalin killed fowl cholera vaccine. The efficacy of the newly prepared vaccine was determined in Starcross-579 chickens (n=30) aging 15 weeks either by injecting 1 mL (group-A;  n=10)  or  0.5  mL  (group-B;  n=10)  vaccine  containing  approximately 3.2x10 8  CFU/mL P. multocida organism; 10 birds were kept as unvaccinated control. The sera from the vaccinated and control birds were collected and were subjected for antibody titre determination by enzyme-linked immunosorbent assay (ELISA). Finally the vaccinated birds were challenged using virulent strains of P. multocida to confer the protection against FC.  Results:  P.  multocida could be  isolated  from  both the  samples.  The  formalin  killed vaccine prepared from the isolated bacteria was subjected for the determination of antibody titre in chicken, and found that the antibody titres in the birds of group A and group B were 4.513 and 4.07 respectively after primary vaccination, and 4.893 and  4.37  respectively  after  booster  vaccination.  Most  of  the  vaccinated  birds  were found to be survived after challenging with virulent strain of P. multocida.  Conclusion: It is concluded that the causal agent of FC (P. multocida) was successfully isolated from FC affected dead chickens. The prepared formalin killed fowl cholera vaccine  induces  protective  immune response  and  conferred  protection  against challenge infection caused by the virulent strain of P. multocida.http://dx.doi.org/10.5455/javar.2016.c130